Rational political parties and electoral games: the AKP's strategic move for the Kurdish vote in Turkey. (2nd January 2016) - Arikan Akdağ, Gül
ABSTRACT: Based on spatial modeling, this study introduces the Kurdish Opening policy of the AKP to resolve the Kurdish problem in Turkey as a rational strategy to increase its electoral support. On one hand, through the analysis of the effective numbers of parties, margins of victory in the Kurdish populated region and provinces it shows that the AKP and the pro-Kurdish parties are the main competitors among Kurdish voters, yet the competition the two parties face is not uniform across the provinces. On the other hand, shifts in Islamist vote and volatility rates indicate the presence of a large amount of religiously oriented ethnic voters who are sensitive to positional change especially in the provinces where the AKP is overrepresented in the parliament. More generally, the study confirms that the AKP's move on the Kurdish issue should be evaluated as a rational strategy that increases the number of potential swing voters for the party.